Educating engineering designers for a multidisciplinary future - Bergström, Mattias; Ericson, Åsa; Matzen, Detlef; Tan, Adrian (Luleå tekniska universitet, Innovation och Design, 2007)
Contemporary companies on a global market are experiencing constantly changing business demands and increased competition. Increasing focus in product development is now put on issues like understanding users and their needs, the context where users’ activities take place and creating sustainable solutions (McAloone, et.al., 2007). In manufacturing companies, engineering designers play a significant role in realising what is captured in these words.Future engineering designers will hold wider responsibilities for such tasks (McAloone, et.al., 2007; Larsson, et.al., 2005), thus challenging current engineering design education. Educating engineering designers today significantly differs from traditional engineering education (McAloone, et.al., 2007). However, a broader view of design activities gains little attention. The project course Product/Service-Systems, which is coupled to the lecture based course Product life and Environmental issues at the Technical University of Denmark (DTU) and the master programme in Product Development at the Luleå University of Technology (LTU), Sweden, are both curriculums with a broader view than traditional (mechanical) engineering design. Based on these two representatives of a Scandinavian approach, the purpose in this presentation is to describe two ways of educating engineering designers to enable them to develop these broader competencies of socio-technical aspects of engineering design. Product Development at LTU A process, called Participatory Product Innovation (P2I) underpins the master programme Product Development and originates from the Design for Wellbeing (DfW) framework (Larsson, et.al., 2005). This is an inclusive framework which seeks to bring together business, human issues and technology in a comprehensive approach to support the creation of tomorrow’s innovations. A main principle is that many different disciplines should contribute to spur innovation by collaboration across disciplines (Larsson, et.al., 2007). The P2I process starting position is in ...